Nanocatalysts Unravel the Selective State of Ag. Issue 11 (7th May 2020) - Lamoth, Maximilian; Jones, Travis; Plodinec, Milivoj; Machoke, Albert; Wrabetz, Sabine; Krämer, Michael; Karpov, Andrey; Rosowski, Frank; Piccinin, Simone; Schlögl, Robert; Frei, Elias
Abstract: In the present work, we report on a comparative study of model catalysts during ethylene epoxidation reaction under industrially relevant conditions. The catalysts consist of Ag nanoparticles <6 nm and a reference sample ∼100 nm. Combining catalytic data with transmission electron microscopy, thermal desorption spectroscopy, and density functional theory allows us to show that catalytic performance is linked to the oxygen concentration in/on the Ag particles. Isotope experiments using 18 O2 and C 18 O2 are conducted to gain insight into the nature and location of oxygen in/on the Ag nanoparticles. The oxygen species responsible for the CO2 formation and inhibition of the overall catalytic activity are identified, and the abundance of those species is shown to depend strongly on the pre‐treatment and reaction conditions, showing both are critical for effective oxygen management. By comparison with a conventional Ag/ α ‐Al2 O3 catalyst, we demonstrate a low concentration of oxygen in/on Ag leads to the highest selectivity regardless of particle size. However, particle size dependent oxophilicity leads to significantly lower TOFs for the Ag nanoparticles. This study provides fundamental understanding of the performance of supported Ag particles in ethylene epoxidation and offers new strategies to improve performance under industrially relevant conditions. Abstract : Ag−O interaction : This study provides fundamental understanding of the performance of supported Ag particles in ethylene epoxidation and offers new strategies to improve performance under industrially relevant conditions.